2010
DOI: 10.1016/j.jmwh.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Gynecologic Cancer Screening: An Integrative Literature Review

Abstract: Further research is needed to clarify the challenges that obese women face in accessing care and to evaluate strategies such as ensuring the availability of appropriate equipment and supplies, the use of alternative screening methodologies, and more culturally sensitive counseling approaches that may improve screening rates in obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
67
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 65 publications
9
67
1
1
Order By: Relevance
“…Our findings on the association between being overweight or obese and higher Pap smear screening is in agreement with only one study (Yancy et al 2010). On the other hand, our findings differ from many other studies where being overweight or obese was associated with lower Pap smear screening (Aldrich & Hackley, 2010;Cohen et al, 2008;Fontaine et al, 1998;Maruthur et al, 2008;Mitchell et al, 2008;Park et al, 2012;Tekkel et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings on the association between being overweight or obese and higher Pap smear screening is in agreement with only one study (Yancy et al 2010). On the other hand, our findings differ from many other studies where being overweight or obese was associated with lower Pap smear screening (Aldrich & Hackley, 2010;Cohen et al, 2008;Fontaine et al, 1998;Maruthur et al, 2008;Mitchell et al, 2008;Park et al, 2012;Tekkel et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…In the total study sample, we found that women who were underweight were less likely to have had a mammogram, a breast self-exam, and a Pap smear, relative to women of normal weight. However, overweight or obese women were more likely to have a breast self-exam and a Pap smear; so, these findings are in disagreement with most of other studies in the literature (Aldrich & Hackley, 2010;Cohen et al, 2008;Edwards et al, 2010;Ferrante et al, 2007;Fontaine et al, 1998Fontaine et al, , 2001Ludman et al, 2010;Maruthur et al, 2008Maruthur et al, , 2009Mitchell et al, 2008;Østbye et al, 2005;Park et al, 2012;Tekkel et al, 2011;Zhu et al, 2006).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Nelson et al reported that smokers, obese women and women with psychological distress participated less often in CC screening (Nelson et al, 2009). Obesity was shown to be a predictor of lower CC screening attendance in a variety of studies; nonetheless, opposite or null results between obesity and screening participation were observed in some other studies (Aldrich and Hackley, 2010;Cohen et al, 2008). A systematic review came to the conclusion that perceived screening facilities--related barriers and perceived psychological barriers to CC screening were associated with lower screening participation (Bukowska--Durawa and Luszczynska, 2014).…”
Section: Introductionmentioning
confidence: 99%